2020
DOI: 10.1101/2020.05.19.20103788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Mental Health Problems During Virus Epidemics in the General Public, Health Care Workers and Survivors: A Rapid Review of the Evidence

Abstract: Background: The swift spread of SARS-CoV-2 provides a challenge worldwide. As a consequence of restrictive public health measures like isolation, quarantine, and community containment, the provision of mental health services is a major challenge. Evidence from past virus epidemics and the current SARS-CoV-2 outbreak indicate high prevalence rates of mental health problems (MHP) as short- and long-term consequences. However, a broader picture of MHP among different populations is still lacking. Methods: We cond… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 116 publications
(139 reference statements)
0
5
0
1
Order By: Relevance
“…This is particularly the case during this pandemic as various confounding factors need to be considered when trying to get a clearer perspective on the complexity of mental health problems in such a crisis. No valid instrument (7) Data not extractable (6) Not general population (5) Only one time point during/after lockdown (5) Valid instrument in one wave only (1) No data from lockdown (1) Review paper (1) Duplicate data (1) Studies included in qualitative synthesis (n = 23)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly the case during this pandemic as various confounding factors need to be considered when trying to get a clearer perspective on the complexity of mental health problems in such a crisis. No valid instrument (7) Data not extractable (6) Not general population (5) Only one time point during/after lockdown (5) Valid instrument in one wave only (1) No data from lockdown (1) Review paper (1) Duplicate data (1) Studies included in qualitative synthesis (n = 23)…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemics had tremendous negative consequences on the mental health of various population groups such as health care workers and survivors of the infectious disease. However, past epidemics have also negatively impacted the mental health of general populations at large 1 . Therefore, during the first wave of the Coronavirus pandemic and the first phase of lockdowns, there were widespread fears concerning mental health problems beyond population groups that were directly affected by the illness 2 .…”
mentioning
confidence: 99%
“…As the pandemic and public health measures escalated, experts in various fields quickly began to note the probability of negative impact on mental health in the general public and the need for additional or improved mental health services [ 2 , 3 , 4 , 5 ]). Indeed, the probability that COVID-19 will have at least short-term negative effects on mental health among the U.S. general public is suggested by research from prior pandemics, especially SARS-CoV-1 [ 6 ] and by recently-published studies (for a review, see [ 7 ]), especially those conducted with Chinese citizens who first experienced the pandemic’s outbreak and their government’s extensive measures to prevent the disease from spreading [ 8 , 9 , 10 , 11 , 12 , 13 ]. These studies document detrimental effects of COVID-19 on depression, anxiety, post-traumatic stress, and sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…12 One review study of viral epidemic impacts revealed that the pooled anxiety and depression prevalence was 45% and 38%, respectively and high impacts were associated with female gender and younger age. 13 Generally, existing materials pointed out that, the occurrence of psychological distress due to the pandemic is heterogeneous 14 and individuals with a chronic medical illness were anticipated to have high levels of anxiety and depression. 12 Therefore, this study aimed to measure the prevalence of depression and anxiety among people with a chronic medical condition during the COVID-19 pandemic as they are one of the at risk groups.…”
Section: Introductionmentioning
confidence: 99%